Clinical profile of Dengue fever in an urban tertiary care hospital in South India - P., Dhivya; A., Monica; S., Jayaramachandran (International Journal of Advances in Medicine, 2019)
Background: Dengue is among the most common flavivirus infections in the world. Today dengue ranks as the most important mosquito- borne viral disease in the world. Current estimates report that, at least 112 countries are endemic for Dengue and about 40% of the world populations (2.5-3 billion people) are at risk in tropics and subtropics. Annually 100 million cases of dengue fever and half a million cases of DHF occur worldwide. The clinical features are noted to be different in varying demographics of the world outlining the importance of bringing out data from different parts of the world, so clinicians are better equipped to anticipate the problems associated with clinical dengue. Methods: The study was conducted over a period of 2 years at a tertiary care hospital in urban Bengaluru, India. A cross sectional study of a total of 250 patients was done. They were diagnosed to be positive for dengue serology (NS1 or IgM) before including them in the study. Clinical features, haematological, biochemical and radiological parameters were assessed. Results: Out of 250 patients with dengue fever, the most common symptoms were fever (100%), headache (94.4%) and myalgia (97.2%). Bleeding manifestations were noted in 11.6% of the patients. Bradycardia was noted in 14.8% of the study population. Leukopenia was noted in 36% of the study population. Increased SGOT was seen in 59.6% and increased SGPT in 52.8% of the 250 subjects. The clinical outcome of the 250 patients of dengue fever was classical dengue fever in 86.8%, DHF in 11.6%, DSS in 0.8% and death in 0.8%. Conclusions: All patients with dengue fever present with fever. Other common features noted were headache, myalgia. Bleeding manifestations are to be looked out for. Rare but important features that a clinician must be vigilant to look for are bradycardia and leucopenia.